Demanding Occupations and the Retirement Age - Niels Vermeer; Mauro Mastrogiacomo; Arthur van Soest (Institute for the Study of Labor (IZA), 2015)
In several countries where pensions are reformed and the retirement age is increased, the issue came up to make an exception for workers with demanding occupations, since health considerations may make it unreasonable to expect them to work longer. We analyze unique Dutch survey data on the public's opinions on what are demanding occupations, on whether it is justified that someone with a demanding occupation can retire earlier, and on the willingness to contribute to an earlier retirement scheme for such occupations through higher taxes. A representative sample of Dutch adults answered several questions about hypothetical persons with five different jobs. We use panel data models, accounting for confounding factors affecting the evaluations of the demanding nature of the jobs as well as their reasonable retirement age or willingness to contribute to an early retirement scheme. We find that the Dutch think that workers in demanding occupations should be able to retire earlier. A one standard deviation increase in the perceived demanding nature of an occupation translates into a twelve months decrease in the reasonable retirement age and a 30 to 40 percentage points increase in the willingness to contribute to an early retirement scheme for that occupation. There is some evidence that respondents whose own job is similar to the occupation they evaluate find this occupation more demanding than other respondents, but respondents are also willing to contribute to early retirement of demanding occupations not similar to their own.
Keywords: J26; J81; H55; 330; retirement age; public pensions; job characteristics; social preferences